Unplugged Coding and Tri Hita Karana in Fostering Thinking and Environmental Awareness - Ni Wayan Rati; I Gde Wawan Sudatha; Kadek Ari Dwiarwati; Kadek Yogi Parta Lesmana; Esaputra, I Nyoman Tri; C. Chiu (Jurnal Pendidikan IPA Indonesia, 2025)
The increasing demand for Computational Thinking (CT) and Environmental Awareness (EA) in elementary science education highlights the need for innovative and culturally relevant learning approaches. However, traditional science teaching methods often emphasize rote memorization rather than problem-solving and ecological responsibility, leading to a lack of deeper conceptual understanding among students. This study investigates the influence of Unplugged Coding Learning integrated with Tri Hita Karana (THK) spiritual values on the development of CT and EA in elementary school students. This research employs a quasi-experimental design with a pretest-posttest control group approach. Data were collected using multiple-choice assessments for CT and EA and were analyzed using Multivariate Analysis of Variance (MANOVA) to determine the effectiveness of the intervention. The results indicate that students who participated in Unplugged Coding Learning with THK values demonstrated significantly higher gains in CT skills (logical reasoning, problem-solving, and pattern recognition) and EA (understanding sustainability and conservation principles) compared to the control group. The Palemahan aspect of THK, which emphasizes harmony with nature, contributed to students’ increased awareness of environmental issues. These findings suggest that integrating local wisdom into STEM education enhances both cognitive and ethical development. The study implies that culturally embedded educational approaches can bridge computational problem-solving skills with environmental consciousness, fostering a more holistic learning experience. Future research should explore long-term impacts and adaptability of this model across different educational settings.